Socio-economic and travel characteristics of transit users at transit-oriented development (TOD) stations - Jaffar Sidek, Mohd Farid; Bakri, Fatahsha Amira; Kadar Hamsa, Abdul Azeez; Nik Othman, Nik Nurul 'Aziemah; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (2019)
The level of motorization has been increasing at an alarming rate in Malaysia over the years. Increase in population, economic growth, affordability to purchase vehicles, low fuel price, attractive vehicles financing system are some factors causing growth in motorization. As a result, Klang Valley and its conurbation is overwhelmed by traffic jams, where people tend to travel by their own cars. To provide a productive solution for these massive issues, it is important to identify the factors influencing the transit users to choose the LRT services as their mode of transport. Some of the factors are related with socio economic and travel characteristics. The objective of this study is to identify the factors affecting to select the LRT services as the transportation mode for their travel activities in the aspects of demographic and travel pattern of the transit users. A survey was conducted to 3 stations in Kelana Jaya line and 3 stations in Ampang Line. The questionnaires were distributed to the passengers who access to/from the selected TOD stations. The questionnaire survey covers area such as location of origin and destination, types of activities at origin and destination, and mode of transport used to reach the TOD stations. From this study, the willingness travel distance, important types of activities at origin and destination point, and major mode of transport to access to/from TOD stations were identified. The findings were made in comparison to the literature and the output was presented in appropriate digital mapping images. Recommendations are to realize the acceptable travel distance and mode of transport choice as well as the major land uses activities for the improvement of TOD stations in Kuala Lumpur.